Incisional hernia: conventional open mesh versus laparoscopic repair; a randomized controlled study - Alsubaiee, Ibrahim F. (International Surgery Journal, 2020)
Background: Incisional hernia is a common complication after laparotomy. Up to now, there is no consensus on the ideal surgical approach of such hernia. The aim of the present study was to compare the surgical outcomes, feasibility and cost effectiveness of the open mesh repair and laparoscopic repair of incisional hernia. Methods: A randomized controlled study conducted between August 2015 and September 2019 in which 64 patients with incisional hernias were randomly selected for either open mesh repair (36 patients) or laparoscopic repair (28 patients). Results: Patients in both groups were similar in their characteristics. The mean operative time was significantly longer in laparoscopic repair than in open mesh repair (128.6±15 minutes versus 89.8±82 minutes, p<0.05). The peri-operative complications and intra-operative blood loss were comparable in the two groups. The use of the drain was significantly higher in open group than in laparoscopic repair group (44.4% versus 10.7%). The overall rate of postoperative complications was similar in both groups, (25% for each group). The rate of wound infection and the length of hospitalization were significantly less in laparoscopic repair group. The results of postoperative pain score, cosmetic outcomes and recurrence rate showed no significant differences between the two groups but patient’s satisfaction was significantly higher in laparoscopic repair. p>0.05. Conclusion: Both laparoscopic and conventional open mesh repair of incisional hernia are equivalent and feasible and safe technique. Laparoscopic repair was superior to open mesh repair in term of surgical site infection, hospital stay and patient’s satisfaction only.